Neuroinflammation decreased hippocampal microtubule dynamics in the acute behavioral deficits induced by intracerebroventricular injection of lipopolysaccharide in male adult rats. Issue 7 (5th May 2021) - Wu, Zuotian; Wang, Gaohua; Zhou, Lin; Sun, Limin; Xie, Yumeng; Xiao, Ling
Abstract : Neuroinflammation plays a vital role in the pathology of depression. Microtubule dynamics produces an immediate response to stress, but the effect of microtubule dynamics in the rats with acute behavioral deficits following a central immune challenge remains elusive. Adult male Sprague–Dawley rats were subjected to the intracerebroventricular (icv) injection of lipopolysaccharide (. Behavioral tests, including bodyweight, sucrose preference test (SPT), forced swimming test (FST) and open field test (OFT), were performed to evaluate anxiety-like and depressive-like phenotypes at 24 h after injection, and some neuroinflammation biomarkers and microtubule dynamics in the hippocampus were detected. Lipopolysaccharide decreased the bodyweight, sucrose preference in SPT (depressive-like behavior), spontaneous activity in OFT (anxiety-like behavior) and increased the immobility time in FST (depressive-like behavior). Besides, lipopolysaccharide increased the mRNA levels of hippocampal CD11b and ionized calcium binding adaptor molecule (Iba1), which suggest microglial activation, and also upregulated hippocampal NLR Family Pyrin Domain Containing 3 inflammasome/interleukin-18/nuclear factor kappa-B mRNA. Lipopolysaccharide injection(icv) reduced the ratio of Tyr-/Acet-tubulin, an important marker of microtubule dynamics, in the acute behavioral deficit rats. Specifically, a decrease in Tyr-tubulin and an increase in the expression of Acet-tubulin were observed, indicating weakened microtubule dynamics. Pearson correlation analysis further showed that there was a significant negative correlation between hippocampal microtubule dynamics and neuroinflammatory activity. This study confirmed that hippocampal microtubule dynamics was decreased in the rats with acute behavioral deficits following a central immune challenge.